2010
DOI: 10.1007/s00586-010-1331-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric trajectory analysis for the C2 crossing laminar screw technique

Abstract: This paper reports a morphometric study of the C2 laminae to provide quantitative anatomical data for safe crossing laminar screw placement. A valid trajectory is essential for C2 crossing laminar screw placement. Although several clinical technique notes and modifications to define a safe screw trajectory have been introduced in the recent years, no morphometric analysis has been performed to confirm the accuracy of screw trajectory using this technique. In this study, morphometric analysis was performed on 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
(24 reference statements)
0
9
0
2
Order By: Relevance
“…The data from general population may not apply to patients with OO. In addition, the use of C2 laminar screws in atlantoaxial fixation in attempt to reduce the risk for the vertebral artery (VA), was first reported by Wright et al [36] in 2004 and since became popular [18,19,38]. For OO patients, however, a couple of questions arise: can C2 pedicle screw be safely placed in every OO patient?…”
Section: Introductionmentioning
confidence: 99%
“…The data from general population may not apply to patients with OO. In addition, the use of C2 laminar screws in atlantoaxial fixation in attempt to reduce the risk for the vertebral artery (VA), was first reported by Wright et al [36] in 2004 and since became popular [18,19,38]. For OO patients, however, a couple of questions arise: can C2 pedicle screw be safely placed in every OO patient?…”
Section: Introductionmentioning
confidence: 99%
“…после фиксации C 1 -C 2 по Harms: ротация в шейном отделе сочетается с флексионным компонентом (движения происходят за счет субаксиальных сегментов) ХИРУРГИЯ ПОЗВОНОЧНИКА Повреждения позвоночника 2/2014 (С. [42][43][44][45][46][47][48] А.В. Губин и др.…”
Section: рисunclassified
“…Траектория введения соответствует 50° в аксиальной плоскости. При этом оптимальная длина винта составляет 20-22 мм [42]. Данных о повреждениях невральных структур и позвоночных артерий при трансламинарном способе введения винтов в С 2 в литературе обнаружить не удалось.…”
Section: рисunclassified
“…The screws can be inserted without breaching into spinal canal if the angle of insertion is ≥50° laterally. The reported maximum safe length of translaminar screws ranged from 21mm to 28mm, 21,23,25 which is slightly shorter than the transpedicular screws but significantly longer than trans pars screws. However, the recent radiological and cadaveric studies reported that the width of C2 lamina was <5mm in 15-29% of cases.…”
mentioning
confidence: 93%